Reactivity and Applications of Iodine Monochloride in Synthetic Approaches. Issue 30 (22nd June 2021) - Day, David P.; Alsenani, Nawaf I.; Alsimaree, Abdulrahman A.
Abstract: Over the last half‐decade, routes towards accessing halogenated compounds of value such as bioactive pharmaceuticals, organic building blocks has been of interest to the synthetic community. The demand for new methodologies to access important compounds has surged over the period. Amongst the halogenating agents available in a chemist's toolbox, one reagent in particular, iodine monochloride (ICl), is relatively under employed in comparison to alternatives such as molecular iodine for example. In this Minireview, we document the most recent applications (2015–2020) of ICl in synthetic organic transformations, namely halogenations including iodinations and chlorination reactions, cyclizations, metathesis reactions as well as oxidation processes. Furthermore, its versatile nature and interesting properties will be discussed, through its advantages and downfalls over other halogenating reagents, and discussions where relevant to compare modes of reactivity and mechanistic insights is presented. Abstract : The demand for discovering new protocols to conduct reactions including halogenations, oxidations and cyclizations has recently led to a renaissance in studying reactions involving somewhat forgotten halogen‐containing reactants. This Minireview documents the processes that have employed iodine monochloride, an intriguing, highly polarized compound composed of sole iodine and chlorine atoms.